Tracing Genealogies: Toward an International Multicultural Anthropology - James Fox (Antropologi Indonesia, 2002)
"Tracing intellectual genealogies should be of particular interest to anthropologists. Genealogies are recognized as a significant way to link generations, to recognize predecessors and to trace origins. They are thus a primary basis for acknowledging participation in a tradition. The Islam tradition of learning, for example, though its use of isnad gives central importance to genealogy in affirming critical intellectual succession. And certainly in the much briefer tradition of anthropology, which only began to take shape in the early twentieth century, anthropologists were taught to make use of the 'Genealogical Method' as a means of research as well as a means of understanding."